A Novel Psychotherapy Effect Detector of Public Art Based on ResNet and EEG Imaging. (7th April 2022) - Tian, Tingyi; Wang, Le; Luo, Man; Zhu, Wei
Abstract : Background and Objective . In view of the imperfection of the current public art evaluation system and practical utility detection system, this paper designs and invents a psychotherapy effect detector of public art based on ResNet network and EEG imaging. The detector includes sensor signal acquisition unit, signal storage and transmission unit, and human-computer interaction visualization unit. The detector is designed in order to test the psychotherapy effect of public art and quantify the public's evaluation of public art to improve the public art evaluation system. Methods . The EEG emotion dataset seed is used for feature extraction with DE, and the emotion is recognized by ResNet. Adam optimizer is used to classify the extracted DE through ResNet50 model. Each batch is set as 5 groups of data and is trained for 50 rounds, then the model is optimized, and the accuracy rate is 76.47%, which output the probability of good emotion through the model. We put the model optimized by ResNet into the intelligent module and visualize it with numerical value. Results . The detector designed by EEG data and ResNet50 optimization model has high accuracy. The results show that the error between the detector data and the questionnaire interview data is small, the average error is 2.77, and the accuracy is 97%. The closer the subject's emotion before the test is to neutral emotion, the closer the questionnaire result is to the test result of the tester, and the smaller the error is. The difference between the tester data and the survey questionnaire data is 0.2, which is in good agreement and has small error. It can be seen that the detector has high accuracy. Conclusion . Our proposed public art psychotherapy effect detector has good accuracy in detecting users' emotions. It can detect the group psychotherapy effect of public art and can classify and screen a large number of public arts in the city by quantitative methods. It provides support for further summarizing the practical utility of public art and provides a new way for the optimal design and follow-up evaluation of public art design.